Reintroducing beavers Castor fiber to Britain: a disease risk analysis. (25th June 2019) - Girling, Simon J.; Naylor, Adam; Fraser, Mary; Campbell‐Palmer, Róisín
Abstract: Eurasian beavers Castor fiber are potential hosts for a range of infectious diseases and parasites, including those typical of common European rodents. A number of infectious organisms are potentially zoonotic and may be notifiable under animal health legislation. The official trial beaver reintroductions to Scotland, the retrospectively licensed releases in England, and the increasingly obvious presence of large numbers of unlicensed illegally released animals have highlighted potential disease risks. We aimed to conduct a disease risk analysis, based on peer reviewed publications, for selection and health screening of Eurasian beavers prior to release into the wild in Britain. Adapted from the International Union for the Conservation of Nature's 'Guidelines for Disease Risk Analysis', a four‐step process was used to formulate a disease risk analysis: 1) problem description; 2) hazard identification based on literature review; 3) risk assessment, which resulted in categorisation of pathogens into low, medium, and high risk; and 4) risk management: identification of mitigating measures, followed by risk re‐evaluation in light of the reported effectiveness of the mitigation measures. The highest‐risk pathogens identified in the literature review process included: parasites, specifically Cryptosporidium parvum, Echinococcus multilocularis, Eimeria spp., Fasciola hepatica, Giardia spp., Trichinella britovi ; bacteria, specifically Escherichia coli, Franciscella tularensis, Mycobacterium avium, Salmonella spp., Yersinia spp.; a fungus Chrysosporium parvum ( Emmonsia parva ); and terrestrial rabies virus. Most could be mitigated by sourcing beavers from Britain. The rest could be mitigated by pre‐release testing procedures that are already established. The risk of introducing significant disease to humans, domestic animals, or wildlife by releasing into the wild in Britain a beaver that was captive‐bred in Britain or a wild beaver from Scotland, based on the current evidence of disease incidence, and assuming the use of robust, peer reviewed, pre‐release health screening techniques, can be viewed as low.